2017
DOI: 10.1093/mnras/stx746
|View full text |Cite
|
Sign up to set email alerts
|

Limiting magnetic fields in the cosmic web with diffuse radio emission

Abstract: We set limits on the presence of the synchrotron cosmic web through the crosscorrelation of the 2.3 GHz S-PASS survey with a model of the local cosmic web derived from constrained magnetohydrodynamic (MHD) simulations. The MHD simulation assumes cosmologically seeded magnetic fields amplified during large-scale structure formation, and a population of relativistic electrons/positrons from proton-proton collisions within the intergalactic medium. We set a model-dependent 3σ upper limit on the synchrotron surfac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 62 publications
2
63
0
Order By: Relevance
“…We can still compare this limit to other limits and estimates. Vernstrom et al (2017) and Brown et al (2017) estimated upper limits on the magnetic field of the IGM using cross-correlation analyses and found limits of ∼ 100 to ∼ 500 nG. The recent work by Vacca et al (2018) found an average magnetic field in the IGM from simulations of 20−50 nG, with previous simulations finding similar values of ∼ 10 − 50 nG (Ryu et al 2008;Vazza et al 2014bVazza et al , 2016.…”
Section: The Igm Contributionmentioning
confidence: 88%
“…We can still compare this limit to other limits and estimates. Vernstrom et al (2017) and Brown et al (2017) estimated upper limits on the magnetic field of the IGM using cross-correlation analyses and found limits of ∼ 100 to ∼ 500 nG. The recent work by Vacca et al (2018) found an average magnetic field in the IGM from simulations of 20−50 nG, with previous simulations finding similar values of ∼ 10 − 50 nG (Ryu et al 2008;Vazza et al 2014bVazza et al , 2016.…”
Section: The Igm Contributionmentioning
confidence: 88%
“…Upper limits have been found so far with correlation techniques between radio emission and cosmic web tracers (e.g. Vernstrom et al 2017;Brown et al 2017) and a possible detection of diffuse synchrotron emission from a filament has recently been reported using the 64-m Sardinia Radio Telescope in combination with interferometric data to subtract blended compact sources (Vacca et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The large-scale structure of the Universe requires the presence of intergalactic shocks, which are in turn expected to accelerate electrons and amplify intergalactic magnetic fields (Keshet et al, 2004b;Brüggen et al, 2005;Hoeft & Brüggen, 2007;Battaglia et al, 2009;Araya-Melo et al, 2012). These shocks should thus produce faint synchrotron emission, which can act as a tracer of large-scale structure, cosmic filaments and primordial magnetic fields (Keshet et al, 2004a;Wilcots, 2004;Donnert et al, 2009;Vazza et al, 2015a,b;Brown et al, 2017b). Detection of this "synchrotron cosmic web" can provide a direct image of the large-scale structure of the Universe, act as a laboratory for studying particle acceleration in low-density shocks, lead to a measurement of the magnetic field strength of the intergalactic medium, and provide a direct discriminant on competing models for the origin of cosmic magnetism.…”
Section: The Synchrotron Cosmic Webmentioning
confidence: 99%
“…The depth of the search reported by Vernstrom et al (2017) was limited by confusion, in that large numbers of unresolved extragalactic radio sources have not been subtracted from the data, and may mimic diffuse radio emission that traces large-scale structure. As for many other continuum science programs, the improved angular resolution and reduced confusion levels offered by MWA Phase II will enable much deeper searches for the synchrotron cosmic web, whether by direct imaging (e.g., Kronberg et al, 2007), statistical cross-correlations (Vernstrom et al, 2017;Brown et al, 2017b) or also in polarimetry Brown et al, 2009).…”
Section: The Synchrotron Cosmic Webmentioning
confidence: 99%